The Plain Sense of Exodus 23:5 - Cooper, Alan (Hebrew Union College annual, 1988)
Since antiquity, commentators have taken Exodus 23:5 to impose a duty of assistance upon a person who encounters an enemy's animal in distress. This misunderstanding of the text is already to be found in Deuteronomy 22:4 and in the Septuagint. It was (and still is) often propounded for apologetic purposes, although it depends on problematic or unacceptable interpretations of the verb ʿ-z-b. If ʿ-z-b is taken in its normal sense ('leave, forsake, abandon'), then, in contrast to the preceding verse, Exodus 23:5 describes a situation in which one must avoid any contact with an enemy's animal. Following a detailed discussion of the history of interpretation (including an Appendix on the meaning of ʿ-z-b), the author musters philological, rhetorical, and juridical arguments in support of this new interpretation of the law.